Characterising co-infections with Plasmodium spp., Mansonella perstans or Loa loa in asymptomatic children, adults and elderly people living on Bioko Island using nucleic acids extracted from malaria rapid diagnostic tests. - Charlene Aya Yoboue; Salome Hosch; Olivier Tresor Donfack; Etienne A Guirou; Bonifacio Manguire Nlavo; Mitoha Ondo'o Ayekaba; Carlos Guerra; Wonder P Phiri; Guillermo A Garcia; Tobias Schindler; Claudia A Daubenberger (Public Library of Science (PLoS), 2022)
Background Regular and comprehensive epidemiological surveys of the filarial nematodes Mansonella perstans and Loa loa in children, adolescents and adults living across Bioko Island, Equatorial Guinea are lacking. We aimed to demonstrate that blood retained on malaria rapid diagnostic tests, commonly deployed for malaria surveys, could be used as a source of nucleic acids for molecular based detection of M. perstans and L. loa. We wanted to determine the positivity rate and distribution of filarial nematodes across different age groups and geographical areas as well as to understand level of co-infections with malaria in an asymptomatic population. Methodology M. perstans, L. loa and Plasmodium spp. parasites were monitored by qPCR in a cross-sectional study using DNA extracted from a subset malaria rapid diagnostic tests (mRDTs) collected during the annual malaria indicator survey conducted on Bioko Island in 2018. Principal findings We identified DNA specific for the two filarial nematodes investigated among 8.2% (263) of the 3214 RDTs screened. Positivity rates of M. perstans and L. loa were 6.6% and 1.5%, respectively. M. perstans infection were more prominent in male (10.5%) compared to female (3.9%) survey participants. M. perstans parasite density and positivity rate was higher among older people and the population living in rural areas. The socio-economic status of participants strongly influenced the infection rate with people belonging to the lowest socio-economic quintile more than 3 and 5 times more likely to be L. loa and M. perstans infected, respectively. No increased risk of being co-infected with Plasmodium spp. parasites was observed among the different age groups. Conclusions/significance We found otherwise asymptomatic individuals were infected with M. perstans and L. loa. Our study demonstrates that employing mRDTs probed with blood for malaria testing represents a promising, future tool to preserve and ship NAs at room temperature to laboratories for molecular, high-throughput diagnosis and genotyping of blood-dwelling nematode filarial infections. Using this approach, asymptomatic populations can be reached and surveyed for infectious diseases beyond malaria.